Role of food preoccupation and current dieting in the associations of parental feeding practices to emotional eating in young adults: A moderated mediation study. (1st April 2017) - Williams, Natalie A.; Dev, Dipti A.; Hankey, Maren; Blitch, Kimberly
Abstract: Parental feeding practices reflecting coercive control are related to children's later eating behaviors, but the mechanisms underlying these effects remain poorly understood. This study examined the relationships between recalled childhood experiences of parental pressure to eat and restriction and current food preoccupation, dieting, and emotional eating in a racially diverse sample of college students ( N  = 711). Results revealed that parental restriction, but not pressure to eat, was associated with more emotional eating ( r  = 0.18, p  < 0.0001). Food preoccupation mediated the association between restriction and emotional eating (95% CI [3.6495–7.2231]); however, a moderated mediation model revealed that the strength of the indirect effect of restrictive feeding on emotional eating through food preoccupation was significantly different for dieters and non-dieters (index of moderated mediation = 1.79, Boot SE = 0.79; 95% bias-corrected bootstrap CI [−3.5490 to −0.4515]). These findings provide unique insight into the mechanisms linking parental feeding practices with emotional eating in young adulthood. Future studies attempting to clarify the processes through which child feeding practices impact later eating behaviors should consider the role of current dieting.